2010
DOI: 10.1152/ajpregu.00620.2009
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin 2 modulates the excitability of area postrema neurons in vitro in the rat

Abstract: Despite recent evidence describing prokineticin 2 (PK2)-producing neurons and receptors in the dorsomedial medulla, little is known regarding the potential mechanisms by which this circadian neuropeptide acts in the medulla to influence autonomic function. Using whole cell electrophysiology, we have investigated a potential role for PK2 in the regulation of excitability in neurons of the area postrema (AP), a medullary structure known to influence autonomic processes in the central nervous system. In current-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Certainly, the possible effects of PROK2 dysregulation at the synaptic level remain largely unexplored and might involve complex mechanisms. For example, previous electrophysiological experiments have demonstrated that PROK2 might reduce the GABAergic function 52 53 or modulate voltage-gated ion channels 54 , the balance of which finely regulates intrinsic excitability and synaptic plasticity events. Thus, application of PC1 might rescue LTP impairment in the Tg2576 model by preserving synaptic homeostasis and vulnerability to the PROK2 insult.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the possible effects of PROK2 dysregulation at the synaptic level remain largely unexplored and might involve complex mechanisms. For example, previous electrophysiological experiments have demonstrated that PROK2 might reduce the GABAergic function 52 53 or modulate voltage-gated ion channels 54 , the balance of which finely regulates intrinsic excitability and synaptic plasticity events. Thus, application of PC1 might rescue LTP impairment in the Tg2576 model by preserving synaptic homeostasis and vulnerability to the PROK2 insult.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller peak of PK2 may contribute to potentiating glutamate excitotoxicity, because PK2 is neuro-excitatory (21)(22)(23). The larger PK2 expression at 24 h may have an additional role; this time point also marks the period when upregulation of a number of proinflammatory genes and infiltration of various inflammatory cells, such as monocytes and macrophages, occurs poststroke (3,48).…”
Section: Discussionmentioning
confidence: 99%
“…Since their initial discovery in 2001, multiple physiological roles for PKs have been discovered, including gastrointestinal motility (12), generation of circadian rhythms (14)(15)(16), angiogenesis (17,18) and choroidal neovascularization (19), olfactory bulb neurogenesis (20), neuroexcitation (21)(22)(23)(24), inflammation (25)(26)(27)(28), and reproduction (29,30). Recent evidence implicated PK2 in a human disease in which different point mutations in genes encoding PK2 or its receptor (PKR2) lead to a type of Kallmann syndrome (29), a disease characterized by abnormal olfactory function and underdeveloped gonads caused by a deficiency in hypothalamic gonadotropin-releasing hormones.…”
mentioning
confidence: 99%
“…PK2 has been shown to modulate the electrical activity of neurons through the activation of PKR2 in the area postrema, subfornical organ, and paraventricular nucleus of the hypothalamus [26][28]. Interestingly, PKR2 mRNA is also expressed in the SCN [17], [21], and PKR2 mRNA-containing neurons are clustered in the dorsomedial region of the SCN [20], suggesting that these receptors may play a crucial role in regulating neuronal activity of the SCN.…”
Section: Introductionmentioning
confidence: 99%